2020
DOI: 10.1002/fes3.208
|View full text |Cite
|
Sign up to set email alerts
|

Biochar addition coupled with nitrogen fertilization impacts on soil quality, crop productivity, and nitrogen uptake under double‐cropping system

Abstract: Biochar and inorganic fertilizer when co‐applied have been reported to increase crop yield and enhance soil fertility. However, studies on this complementary effect on soil properties and noodle rice performance in China are still scanty. To investigate the effects of biochar application coupled with inorganic fertilizers on soil sustainability and yield and yield attributes of noodle rice, outdoor pot experiments were conducted in the early and late growing seasons in 2018. The treatment combinations were T1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 99 publications
8
104
0
Order By: Relevance
“…The possible reason for the higher soil quality might be the higher porosity and higher surface area of biochar and a large number of microspores (Jaafar, Clode & Abbott, 2015a;Jaafar, Clode & Abbott, 2015b). Ali et al (2020), Zhang et al (2019), Kuzyakov, Bogomolova & Glaser (2014), and Liang et al (2014) reported similar effects of biochar on the improvement of soil physiochemical properties. In addition, biochar amendments increase the adsorption of Different litters above the curve indicate statistical significance at the (P < 0.05).…”
Section: Soil Qualitymentioning
confidence: 96%
See 3 more Smart Citations
“…The possible reason for the higher soil quality might be the higher porosity and higher surface area of biochar and a large number of microspores (Jaafar, Clode & Abbott, 2015a;Jaafar, Clode & Abbott, 2015b). Ali et al (2020), Zhang et al (2019), Kuzyakov, Bogomolova & Glaser (2014), and Liang et al (2014) reported similar effects of biochar on the improvement of soil physiochemical properties. In addition, biochar amendments increase the adsorption of Different litters above the curve indicate statistical significance at the (P < 0.05).…”
Section: Soil Qualitymentioning
confidence: 96%
“…Full-size DOI: 10.7717/peerj.10311/ fig-7 soil organic molecules, resulting in organic molecule polymerization to form OM through surface catalytic activity (Zhang et al, 2019). Since biochar is derived from biomass, organic materials do not lose many available nutrients during pyrolysis (Ali et al, 2020) Notes. DM, dry matter accumulation; GY, grain yield; N, nitrogen; till, tillering stage; head, heading stage; Mat, maturity stage; S1, early growing season; S2, late growing season.…”
Section: Soil Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al [21] reported that organic manure applications with a high N content and low C: N ratio could mineralize enough N to satisfy the demands for plant growth. However, organic fertilizer is quite low in nutrients and its nutrient releasing ability is also slow to meet plant requirements in a short period of time, therefore manure coupled with synthetic fertilizer has been confirmed to be a better approach to improve and sustain soil fertility and crop production than sole application of manure or synthetic fertilizer [22][23][24].…”
Section: Introductionmentioning
confidence: 99%